Coral Reef Carbonate Chemistry Variability at Different Functional Scales - Takeshita, Yuichiro; Cyronak, Tyler; Martz, Todd R.; Kindeberg, Theodor; Andersson, Andreas J. (Frontiers in Marine Science, 2018)
There is a growing recognition for the need to understand how seawater carbonate chemistry over coral reef environments will change in a high-CO2 world to better assess the impacts of ocean acidification on these valuable ecosystems. Coral reefs modify overlying water column chemistry through biogeochemical processes reflected in thesuch as net community organic carbon production (NCP) and calcification (NCC). However, the relative importance and influence of these processes on seawater carbonate chemistry vary across multiple functional scales (defined here as space, time, and benthic community composition), and have not been fully constrained. Here, we use Bermuda as a case study to assess 1) spatiotemporal variability in physical and chemical parameters along a depth gradient at a rim reef location, 2) the spatial variability of total alkalinity (TA) and dissolved inorganic carbon (DIC) over distinct benthic habitats to infer NCC:NCP ratios (< several km2; rim reef vs seagrass and calcium carbonate (CaCO3) sediments) on diel timescales, and 3) compare how TA-DIC relationships and NCC:NCP vary as we expand functional scales from local habitats to the entire reef platform (10’s of km2) on seasonal to interannual timescales. Our results demonstrate that TA-DIC relationships were strongly driven by local benthic metabolism and community composition over diel cycles. However, as the spatial scale expanded to the reef platform, the TA-DIC relationship reflected processes that were integrated over larger spatiotemporal scales, with effects of NCC becoming increasingly more important over NCP. This study demonstrates the importance of considering drivers across multiple functional scales to constrain carbonate chemistry variability over coral reefs.